Is nuclear economical in comparison to renewables?. (November 2016) - Suna, Demet; Resch, Gustav
Abstract: The European Union is divided on the issue of electricity production. While there is consensus that generation technologies need to be low on greenhouse gas emissions, the question of whether to use renewables or nuclear to meet this power demand is highly controversial. Both options still require financial support and this is not going to change in the near future. This raises the question of where public money should be invested in order to achieve greater economic efficiency: into support for renewable energies (RE) or support for nuclear power plants? This paper sets out to answer this question. The detailed model-based prospective scenario assessment performed in this study provides the basis for estimating future cost developments. After discussing the existing support schemes for renewables, the paper compares these with a nuclear model. The comparison is conducted exemplarily for the United Kingdom (UK) at a country level and for the EU 28 overall. The recent state aid case for the construction of the Hinkley Point nuclear power plant (NPP) in the UK serves as the model for the nuclear option. Highlights: State aids for new nuclear power is compared with incentives for renewables. Hinkley Point C in the UK is considered as example for new nuclear power. Comparison is conducted for the UK at a country level and for the EU 28 overall. Analysis shows that renewable energies are more economical than nuclear power.